Semantic meaning of “zulf” term in the gazelles of Amir Husrav Dehlaviy (on the examples of gazelle) - Yarashov, Sharif (International Journal of Psychosocial Rehabilitation, 2020)
This article is about the symbols of the term “zulf”, literary and lexical explanation, sufiy meanings, historical development, structure, dictionary meaning and semantic features of lingvopoetic explanation on the example of gazelle with rhymes “yakhshi (good)”, “maktub (letter)” and “oshub (quarrel)” by Amir Husrav Dehlavi. Amir Khusrav explains in the gazelle which begins with "zulf" of the word " Зиҳи намуда аз он зулфу холу орази хуб, Яке саводу дувўм нуқтаву савўм мактуб” by means of art of improvisation has given. In this sense, the word “zulf” has created the basis for many poetic symbols as an artistic element in this ghazal. Creation of logical symbols, based on the figurative meaning of this word, has given rise to the brilliant description of its semantic meanings.